EATMOT Project: Determinants of Healthy Food Choices – Study Involving 16 Countries - Guiné, Raquel (2024)
The EATMOT Project is a multinational study that was carried out in 16 countries focusing on different eating motivations, taking into account their recognized importance in the definition of people’s dietary patterns. The act of eating is not only determined by physiology such as body needs of nutrients and energy, but also by many other factors that interact in a complex way to shape individual eating habits. Hence, the aim of this project was to investigate the different types of motivations that determine people’s eating patterns, either in relation to their choices or eating habits. To do this, factors linked to food choices were evaluated in the following main areas: health motivations; economic factors; emotional aspects; cultural influences; marketing and commercials or environmental concerns. The study was based on a questionnaire that was prepared purposely for the project, and dully validated. The countries involved in the study were: Argentina, Brazil, Croatia, Egypt, Greece, Hungary, Italy, Latvia, Lithuania, Netherlands, Poland, Portugal (Coordinator), Serbia, Slovenia, Romania and United States of America. The collected results included 11,960 validated respondents, whose data was used to characterize the eating motivations in different parts of the world, including those linked with healthy eating. These results are valuable allies to shape interventions aimed at motivating people towards healthier diets. In the modern era, individuals have been increasingly recognizing the concept of dietary health, and therefore the group and individualized guidance on nutritional and healthy eating habits are becoming more relevant.